2018
DOI: 10.1007/s10552-018-1029-9
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable intake and the risk of recurrence in patients with non-muscle invasive bladder cancer: a prospective cohort study

Abstract: IntroductionThere is some evidence that greater consumption of fruit and vegetables decreases the risk of bladder cancer. The role of fruit and vegetables in bladder cancer recurrence is still unknown.ObjectiveThe role of total fruit and vegetable intake in relation to the risk of developing bladder cancer recurrence in a prospective cohort study.Methods728 patients with non-muscle invasive bladder cancer (NMIBC), who completed self-administrated questionnaires on fruit and vegetable intake at time of diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…In 2 studies on bladder cancer patients, the pre- and postdiagnosis intake of total vegetables, fruit, or both were not related to either all-cause mortality or cancer recurrence ( 38 , 51 ). No association with the consumption of cruciferous vegetables before diagnosis was found either ( 38 ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In 2 studies on bladder cancer patients, the pre- and postdiagnosis intake of total vegetables, fruit, or both were not related to either all-cause mortality or cancer recurrence ( 38 , 51 ). No association with the consumption of cruciferous vegetables before diagnosis was found either ( 38 ).…”
Section: Resultsmentioning
confidence: 96%
“…Finally, a total of 28 articles were included in the systematic review and meta-analysis ( Figure 1 ). Of these, 16 studies were used for the qualitative review ( 36 51 ) and 12 for the quantitative meta-analysis ( 52 63 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many “cancer diets” are often restrictive, avoiding a whole nutrient class (i.e., meat or dairy products) in the misleading belief that certain foods “feed the tumor” [ 10 ]. In the last decades, a growing number of prospective cohort studies [ 11 , 12 , 13 , 14 , 15 , 16 ] have investigated the association between post-diagnostic dietary patterns—such as Western diet (WD) and prudent diet (PD)—or food type—such as meat, dairy products, dietary fiber, nuts—and prognostic outcomes among patients with different cancers. This systematic review aims to investigate possible associations between dietary patterns/choices after cancer diagnosis and prognostic outcomes (i.e., mortality, cancer progression, and recurrence) in patients affected by main solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…An intake of ≥ 1 serving of uncooked broccoli/month (mean 3.9 servings/month) was associated with a reduced risk of CSM (HR 0.43, 95% CI 0.25-0.74) and ACM (HR 0.57, 95% CI 0.39-0.83) compared to an intake of < 1 serving/month. This and two other studies reported no associations between fruit and/or vegetable consumption and recurrence, [94,96] progression, [96] or mortality [95]. Another study reported that heavy areca nut chewing (>10 nuts/day), a practice common among individuals in South Asia, may be associated with an increased risk of recurrence (HR 2.18, 95% CI 1.37-3.47) compared to non-chewing [29].…”
Section: Diet and Supplementsmentioning
confidence: 71%